The cult of beauty : the aesthetic movement 1860-1900 - Victoria and Albert Museum; Musée d'Orsay.; M.H. de Young Memorial Museum; Calloway, Stephen; Orr, Lynn Federle, 1947-; Whittaker, Esmé. (London : V&A Publishing, 2011)
Summary: This book focuses on a period at the end of the nineteenth century when a group of artists, architects and designers found themselves linked by the search for a new Beauty. "The Aesthetic movement", as it came to be known, united romantic bohemians such as Dante Gabriel Rossetti, William Morris and Edward Burne-Jones, along with maverick figures such as James McNeill Whistler. The book brings together the finest pictures, furniture and decorative arts of this extraordinary era, setting them in the context of this glittering cast of characters. This beautiful book also reveals how artists' houses and their extravagant lifestyles became the object of public fascination. The influence of the 'Palaces of Art' created by Rossetti and Morris, Lord Leighton and others led to a widespread revolution in architecture and interior decoration, while Oscar Wilde made his name promoting the idea of 'The House Beautiful'.
Published to accompany the exhibition of the same name held at the V&A, London, 2 Apr-17 Jul 2011; Musée d'Orsay, Paris, 12 Sep 2011-15 Jan 2012; de Young Museum, San Francisco, 18 Feb-17 Jun 2012.
Includes bibliographical references (p. 256-260) and index.
boek